Hyperglycemia is associated with worse 3-year survival in older patients admitted to the intensive care unit after non-cardiac surgery: Post hoc analysis of a randomized trial - Li, Mo; Deng, Chun-Mei; Su, Xian; Zhang, Dan-Feng; Ding, Mao; Ma, Jia-Hui; Wang, Dong-Xin (Frontiers in Medicine, 2022)
Objective: Hyperglycemia is common in critically ill patients after surgery and is associated with worse perioperative outcomes. Yet, the impact of postoperative hyperglycemia on long-term outcomes remains unclear. We therefore analyzed the association between early postoperative hyperglycemia and 3-year overall survival in older patients who were admitted to the intensive care unit after surgery. Methods: This was a post hoc analysis of database obtained from a previous randomized trial and 3-year follow-up. The underlying trial enrolled 700 patients aged 65 years or older who were admitted to the intensive care unit after elective noncardiac surgery. Early postoperative time-weighted average blood glucose was calculated and was divided into three levels, i.e., <8.0 mmol/L, from 8.0 to 10.0 mmol/L, and >10.0 mmol/L. The primary outcome was 3-year overall survival. The association between time-weighted average blood glucose level and 3-year overall survival was analyzed with Cox proportional hazard regression models. Subgroup analyses were also performed in patients with or without diabetes, and in patients following cancer or non-cancer surgery. Results: A total of 677 patients (mean age 74 years, 60% male sex) were included in the final analysis. Within 3 years after surgery, deaths occurred in 22.1% (30/136) of patients with time-weighted average blood glucose <8.0 mmol/L, compared with 35.7% (81/227) of those from 8.0 to 10.0 mmol/L (unadjusted hazard ratio 1.75, 95% CI 1.15 to 2.67, P=0.009), and 36.9% (116/314) of those >10.0 mmol/L (unadjusted hazard ratio 1.91, 95% CI 1.28 to 2.85, P=0.002). After adjustment for confounding factors, the risk of 3-year mortality remained higher in patients with time-weighted average blood glucose from 8.0 to 10.0 mmol/L (adjusted hazard ratio 2.28, 95% CI 1.47 to 3.54, P<0.001) and in those >10.0 mmol/L (adjusted hazard ratio 2.00, 95% CI 1.29 to 3.10, P=0.002). Similar results were obtained in the subgroups of patients without diabetes and patients following cancer surgery. Conclusions: For older patients admitted to the intensive care unit after elective noncardiac surgery, high early blood glucose (time-weighted average blood glucose ≥8.0 mmol/L) was associated with poor 3-year overall survival. The impact of moderate glycemic control on long-term survival deserves further investigation.